THE ANALYSIS OF INDIFERENCE AND THE PRICE ELASTICITY OF DEMAND BETWEEN DIFFERENT CATEGORIES OF AGRICULTURAL PRODUCTS - Vukadinović, Predrag; Damnjanović, Aleksandar; Krstić Ranđić, Jelena (Economics of Agriculture, 2017)
In this paper, the analysis of the price elasticity of demand of four different categories of agricultural products in the Republic of Serbia was described. Differentiating the price and demand of these products by sales points, and using the least squares approximation method, the elasticity for all different agricultural categories was expressed in the functional form. According to this, the coeffcients of elasticity of the price and demand were computed and between different agricultural categories were analyzed. The results we obtained show that the market of agricultural products in Serbia is mostly inelastic because the coeffcients of inelasticity and indifference of demand to change of prices, are dominant. The influence of factors on the elasticity of demand that are not of price character, proved to be very pronounced. The relationship of the two segments of agricultural market (markets and shops) was also analysed and it was demonstrated that these two segments have a slight correlation.